1985
DOI: 10.1042/bj2270239
|View full text |Cite
|
Sign up to set email alerts
|

Calcium transport mechanisms in basolateral plasma membrane-enriched vesicles from rat parotid gland

Abstract: Ca2+ transport was studied by using basolateral plasma membrane vesicles from rat parotid gland prepared by a Percoll gradient centrifugation method. In these membrane vesicles, there were two Ca2+ transport systems; Na+/Ca2+ exchange and ATP-dependent Ca2+ transport. An outwardly directed Na+ gradient increased Ca2+ uptake. Ca2+ efflux from Ca2+-preloaded vesicles was stimulated by an inwardly directed Na+ gradient. However, Na+/Ca2+ exchange did not show any 'uphill' transport of Ca2+ against its own gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Sealed inside-out vesicles took up Ca 2ϩ , implying that the direction of pumping in cells was outward, as has been found for numerous other cell types (Carafoli, 1987;Garrahan and Rega, 1990). The uptake rate by osteoblast plasma membrane vesicles was 9.9 Ϯ 2.3 nmol/mg of protein/min, which falls in the range reported for several other vesicle studies, including red blood cells (Caride et al, 1983), parotid gland (Takuma et al, 1985), neutrophils (Ochs and Reed, 1983), and liver (Kraus-Friedmann et al, 1982). Na ϩ / Ca 2ϩ exchange also exists in osteoblasts (Krieger, 1992;Short et al, 1994) and may contribute in a minor way to the Ca 2ϩ efflux observed, as subsequently discussed.…”
supporting
confidence: 69%
“…Sealed inside-out vesicles took up Ca 2ϩ , implying that the direction of pumping in cells was outward, as has been found for numerous other cell types (Carafoli, 1987;Garrahan and Rega, 1990). The uptake rate by osteoblast plasma membrane vesicles was 9.9 Ϯ 2.3 nmol/mg of protein/min, which falls in the range reported for several other vesicle studies, including red blood cells (Caride et al, 1983), parotid gland (Takuma et al, 1985), neutrophils (Ochs and Reed, 1983), and liver (Kraus-Friedmann et al, 1982). Na ϩ / Ca 2ϩ exchange also exists in osteoblasts (Krieger, 1992;Short et al, 1994) and may contribute in a minor way to the Ca 2ϩ efflux observed, as subsequently discussed.…”
supporting
confidence: 69%
“…A previous report from our laboratory (Takuma et al, 1985) showed that inverted basolateral plasma membrane vesicles accumulate Ca 2+ in the presence of ATP. The Ca 2+ accumulated in the vesicles could be discharged by imposing an inwardly directed Na § gradient, indicating the presence of a Na § 2+ exchange mechanism in the same membrane vesicles and also confirming the plasma membrane origin of the ATP-dependent Ca 2+ transporter.…”
Section: Introductionmentioning
confidence: 73%
“…PREPARATION OF BASOLATERAL MEMBRANE VESICLES BLMV were prepared as described previously (Takuma et al, 1985), with some minor modifications. The procedure, in brief, was as follows.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations